Assessment of dyspnea in sarcoidosis using the Baseline Dyspnea Index (BDI) and the Transition Dyspnea Index (TDI). (January 2022) - Obi, Ogugua Ndili; Judson, Marc A.; Birring, Surinder S.; Maier, Lisa A.; Wells, Athol U.; Lower, Elyse E.; Baughman, Robert P.
Abstract: Introduction: The Borg and Modified Medical Research Council (mMRC) dyspnea scales have been used to evaluate dyspnea in sarcoidosis. The Baseline Dyspnea Index (BDI) and Transitional Dyspnea Index (TDI) are useful for the assessment of dyspnea in COPD. It is not known if the BDI-TDI accurately assesses dyspnea in sarcoidosis patients. Methods: Data was analyzed from the Registry for Advanced Sarcoidosis (ReAS), a multi-national database enrolling patients with advanced sarcoidosis and a comparison group of sarcoidosis patients with non-advanced disease. At baseline, patients completed a BDI questionnaire along with spirometry, 6-min walk distance (6MWD), mMRC, Borg score, fatigue assessment score (FAS) and HRQoL assessments using Kings Sarcoidosis Questionnaire (KSQ) and St Georges Respiratory Questionnaire (SGRQ). At 12-months, patients with advanced disease completed a TDI questionnaire along with the other measures. Correlations between BDI and baseline variables, and between TDI and changes in baseline variables were evaluated. Results: There was significant correlation (p < 0.001 for all) between BDI and baseline 6MWD (rho = 0.336), FVC% (rho = 0.387), FEV1% (rho = 0.285), DLCO% (rho = 0.355), mMRC (rho = −0.721), Borg score (rho = −0.389), FAS (rho = −0.669), SGRQ (rho = −0.785), and KSQ (rho = 0.318 to 0.724). At follow-up, TDI correlated with BDI, but not with changes in pulmonary function or other dyspnea measures. Conclusion: BDI scores correlated with pulmonary function, 6MWD, and other dyspnea measures. TDI scores did not correlate with changes in pulmonary function or other dyspnea measures. BDI may be a useful independent measure of dyspnea in sarcoidosis patients. The role of TDI needs further evaluation in longitudinal studies associated with changes in clinical parameters. Highlights: BDI correlated with pulmonary function, 6MWD and other dyspnea and HRQoL measures. There was no correlation between TDI and change in pulmonary function, 6MWD or other dyspnea measures. There was no significant mean change in TDI, 6MWD or other dyspnea measures in our study. BDI may be a useful independent measure of dyspnea in sarcoidosis patients. The role of TDI in sarcoidosis needs to be further evaluated in longitudinal studies associated with changes in clinical parameters.